Heterogeneous catalytic ozonation of dibutyl phthalate in aqueous solution in the presence of iron-loaded activated carbon. (January 2015) - Huang, Yuanxing; Cui, Chenchen; Zhang, Daofang; Li, Liang; Pan, Ding
Highlights: The form of iron on activated carbon was characterized to be goethite. The catalyst enhanced DBP removal through the transformation of O3 to OH. Mechanism for DBP removal by catalytic ozonation was proposed. Abstract: Iron-loaded activated carbon was prepared and used as catalyst in heterogeneous catalytic ozonation of dibutyl phthalate (DBP). The catalytic activity of iron-loaded activated carbon was investigated under various conditions and the mechanisms of DBP removal were deduced. Characterization of catalyst indicated that the iron loaded on activated carbon was mainly in the form of goethite, which reduced its surface area, pore volume and pore diameter. The presence of metals on activated carbon positively contributed to its catalytic activity in ozonation of DBP. Iron loading content of 15% and initial water pH of 8 achieved highest DBP removal among all the tried conditions. Catalyst dosage of 10 mg L −1 led to approximately 25% of increase in DBP (initial concentration 2 mg L −1 ) removal in 60 min as compared with ozone alone, and when catalyst dosage increased to 100 mg L −1, the DBP removal was further improved by 46%. Based on a comparison of reaction rates for direct and indirect transformation of DBP, the increased removal of DBP in this study likely occurred via transformation of ozone into hydroxyl radicals on the catalyst surface.